2023
DOI: 10.1038/s41598-023-33447-x
|View full text |Cite
|
Sign up to set email alerts
|

The response to stressors in adulthood depends on the interaction between prenatal exposure to glucocorticoids and environmental context

Abstract: Maternal stress during reproduction can influence how offspring respond to stress later in life. Greater lifetime exposure to glucocorticoid hormones released during stress is linked to greater risks of behavioral disorders, disease susceptibility, and mortality. The immense variation in individual’s stress responses is explained, in part, by prenatal glucocorticoid exposure. To explore the long-term effects of embryonic glucocorticoid exposure, we injected Japanese quail (Coturnix japonica) eggs with corticos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Higher levels of glucocorticoids inhibit aggressive behavior ( 76 , 77 ), which agrees with the results from our study. In previous work from our lab, we found that being the target of aggressive behavior increased baseline corticosterone, but only if the individuals were exposed to high levels of maternal corticosterone during embryonic development ( 21 ). This previous study suggested that maternal glucocorticoids may provide for endocrine flexibility in stressful postnatal environments, and in the light of our current work it would be interesting to know if maternal glucocorticoid exposure may also prepare offspring for a stressful environment by increasing affiliative behavior.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Higher levels of glucocorticoids inhibit aggressive behavior ( 76 , 77 ), which agrees with the results from our study. In previous work from our lab, we found that being the target of aggressive behavior increased baseline corticosterone, but only if the individuals were exposed to high levels of maternal corticosterone during embryonic development ( 21 ). This previous study suggested that maternal glucocorticoids may provide for endocrine flexibility in stressful postnatal environments, and in the light of our current work it would be interesting to know if maternal glucocorticoid exposure may also prepare offspring for a stressful environment by increasing affiliative behavior.…”
Section: Discussionmentioning
confidence: 63%
“…At the cellular level, one way that prolonged glucocorticoid exposure may have negative health effects is by increasing oxidative stress ( 14 , 18 21 ). Oxidative stress occurs when reactive oxygen species (ROS), many of which are byproducts of inefficient mitochondrial metabolism, damage biomolecules like DNA, lipids, and proteins ( 22 ).…”
Section: Introductionmentioning
confidence: 99%